PENGARUH PENGAWASAN MANAJER DAN PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN HOTEL ALPHA PEKANBARU) - Kurnia Hariyani; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of managerial oversight and incentives on employee performance partially and simultaneously. This study uses questionnaires as a means of collecting data distributed to 56 respondents on employees Alpha Hotel Pekanbaru. Data from the questionnaire was then processed using descriptive analysis and statistical analysis using SPSS 17.0 by performing validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis (R²) and hypothesis test with t test (partial) and F ( Simultaneous).The results showed that the results of the first hypothesis testing of managerial supervision on employee performance is t arithmetic (5,588)> t table (2,004), meaning that manager control variables significantly influence employee performance. Both provision incentives on employee performance is t arithmetic (6.081)> t table (2,004), meaning that incentives have a significant effect on employee performance. Result of F test count (23,417)> F table (3,17), meaning supervisor manager and incentive giving simultant have significant effect to employee performance.Keywords: Manager Control, Incentives, Employee Performance